‘Integrale geneeskunde’ en de crisis in de huisartsgeneeskunde in Nederland omstreeks 1950? - Bergevoet, Martin (Studium, 2013)
The significance of the concept ‘Integrated medical care’ and the crisis in Dutch general medicine around 1950In the middle of the twentieth century the position of Dutch general medical practice was critical. The medical practitioner felt himself inferior to the consulting physician. Due to a changing morbidity he was faced with complaints and illnesses for which he was not sufficiently trained. Moreover, his income was not in accordance with the increasing workload and was far less than that of the hospital physicians. Due to the efforts of the general practitioners themselves in the indicated period, the professional position and the working conditions improved considerably. The book by professor Arie Querido, Inleiding tot een integrale geneeskunde (‘Introduction to an integrated medical care’), published in 1955, played an important role in this process and will be highlighted in this paper.